Estimation of Stature from Cephalo-Facial Dimensions by Regression Analysis in Gujarati Population - Shah, Twisha; Patel, Manharlal Narbheram; Nath, S; Bhise, Ravindra S; Menon , Shobhana K (Journal of Indian Academy of Forensic Medicine, 2015)
During investigation in cases of missing body parts or unknown identity, the expert is often  required to opine about the personal identification of the body. Stature of a person is a useful indicator of  physical identity. Stature estimation leads to a positive identification of the living or when only cephalo facial are brought under examination. The current study dealt with developing regression equation for  stature estimation from cephalo-facial dimensions and to find out the correlation among body height with  each cephalo-facial dimensions of Gujarati people. This leads to positive identification of the living or  cadaver. Eight cephalo-facial dimensions of 901 Gujarati (676 male and 225 female) namely maximum  head length, maximum head breadth, bizygomatic breadth, bigonial diameter, morphological facial length,  physiognomic facial length, and total cephalo-facial height and biocular breadth along with body height  was measured. It was marked that the mean stature and cephalo-facial measurements of males were  significantly higher than that of females. The correlation coefficient (r) of all cephalo-facial dimensions  were less than 0.5 which means stature estimation from cephalo-facial dimensions is not reliable. Multiple  regression equations are more reliable than linear regression equations.
Keywords: Physical Anthropology; Cephalo-facial dimensions; Stature estimation; Gujarati population